2021
DOI: 10.1002/chem.202102905
|View full text |Cite
|
Sign up to set email alerts
|

Strong Ligand Stabilization Based on π‐Extension in a Series of Ruthenium Terpyridine Water Oxidation Catalysts

Abstract: The substitution behavior of the monodentate Cl ligand of a series of ruthenium(II) terpyridine complexes (terpyridine (tpy) = 2,2':6',2''-terpyridine) has been investigated. 1 H NMR kinetic experiments of the dissociation of the chloro ligand in D 2 O for the complexes [Ru(tpy)(bpy)Cl]Cl (1, bpy = 2,2'-bipyridine) and [Ru(tpy)(dppz)Cl]Cl (2, dppz = dipyrido[3,2-a:2',3'-c]phenazine) as well as the binuclear complex [Ru(bpy) 2 (tpphz)Ru(tpy)Cl]Cl 3 (3 b, tpphz = tetrapyrido[3,2 a:2',3'-c:3'',2''-h:2''',3'''-j]p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
4
0
2
Order By: Relevance
“…Subsequent studies for Ru(Cl) catalytic centres for WOC catalysis at a series of bipyridine and oligopyridophenazine ligands, including the tpphz ligand, clearly demonstrated that π‐conjugation of the BL can significantly strengthen the metal‐halide bond and subsequently prevent the system to undergo loss of the ligand sphere accompanied by particle formation [105] . However, in the case of [(tbbpy) 2 Ru(tpphz)MCl 2 ] 2+ (M=Pt or Pd) only the Pt(II)‐system seems to provide sufficient stability.…”
Section: Instability Of the Catalytic Metal Centre As A Limiting Fact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies for Ru(Cl) catalytic centres for WOC catalysis at a series of bipyridine and oligopyridophenazine ligands, including the tpphz ligand, clearly demonstrated that π‐conjugation of the BL can significantly strengthen the metal‐halide bond and subsequently prevent the system to undergo loss of the ligand sphere accompanied by particle formation [105] . However, in the case of [(tbbpy) 2 Ru(tpphz)MCl 2 ] 2+ (M=Pt or Pd) only the Pt(II)‐system seems to provide sufficient stability.…”
Section: Instability Of the Catalytic Metal Centre As A Limiting Fact...mentioning
confidence: 99%
“…Subsequent studies for Ru(Cl) catalytic centres for WOC catalysis at a series of bipyridine and oligopyridophenazine ligands, including the tpphz ligand, clearly demonstrated that π-conjugation of the BL can significantly strengthen the metal- halide bond and subsequently prevent the system to undergo loss of the ligand sphere accompanied by particle formation. [105] However, in the case of [(tbbpy) 2 Ru(tpphz)MCl 2 ] 2 + (M = Pt or Pd) only the Pt(II)-system seems to provide sufficient stability. Thus, it is tempting to speculate that the different electronic properties of the systems, resulting from the different nature of the CC, have a significant influence on the stability of the photocatalyst during reductive catalysis.…”
Section: Stability Of Di-and Oligonuclear Catalystsmentioning
confidence: 99%
“…金属中心钌的多价态使得三联吡啶钌配合物在催 化领域扮演着重要的角色, 包括二氧化碳还原 [125] 、 水氧 化 [126] 、 芳烃硝基转移加氢 [127] 、 酮到醇的氢转移反应 [128] 、 伯醇的顺序氧化和不对称烷基化 [129] 以及光诱导一氧化 碳 [130] 或一氧化氮分子 [131] 的释放等. 然而, 双三联吡啶 钌配合物的八面体结构导致钌金属中心被包裹在了配 体内部, 难以提供可发挥催化作用的活性位点, 所以在 上述反应过程中发挥催化作用时的结构均为不对称的 单三联吡啶钌配合物.…”
Section: 催化性质unclassified
“…Large but well-behaved parts of the chemical system can be described with low-cost methods, such as force fields, while smaller regions, where quantum effects play an essential role, or high accuracy is required, can be described with more precise but also computationally more demanding quantum mechanical methods. Thus, QM/MM and ONIOM have been successfully employed to describe the photophysics of proteins and deoxyribonucleic acid (DNA), [31][32][33][34] processes in soft matter materials, 35 catalytic processes, [36][37][38] inorganic materials, [39][40][41] reactive chemistry, 42 and more. In recent years, many implementations for QM/MM and ONIOM methods have emerged or have been improved; LiCHEM 43 and QM/MM 44 implement polarizable QM/MM methods, which can improve the description of ground and excited states.…”
Section: Introductionmentioning
confidence: 99%